Epigenetic modulation in the treatment of atherosclerotic disease - Byrne, Mikaela M.; Murphy, Ross T.; Ryan, Anthony W. (Frontiers in Genetics, 2014)
Cardiovascular disease is the single largest cause of death in the western world and its incidence is on the rise globally. Atherosclerosis, characterised by the development of atheromatus plaque, can trigger luminal narrowing and upon rupture result in myocardial infarction or ischemic stroke. Epigenetic mechanisms are a source of considerable research interest due to the role they play in gene regulation. Epigenetic mechanisms such as DNA methylation and histone acetylation have been identified as potential drug targets in the treatment of cardiovascular disease. miRNAs are known to play a role in gene silencing, which has been widely investigated in cancer. In comparison, the role they play in cardiovascular disease and plaque rupture is not well understood. Nutritional epigenetic modifiers from dietary components, for instance sulforaphane found in broccoli, have been shown to suppress the pro-inflammatory response through transcription factor activation. This review will discuss current and potential epigenetic therapeutics for the treatment of cardiovascular disease, focusing on the use of miRNAs and dietary supplements such as sulforaphane and protocatechuic aldehyde.